Does Hip Arthroscopy Provide Meaningful Outcome Improvement for Adolescent Femoroacetabular Impingement - Nwachukwu, Benedict Uchenna (Orthop J Sports Med, 2017)
OBJECTIVES: Arthroscopic treatment of femoroacetabular impingement (FAI) produces meaningful outcome improvement in adults. Hip arthroscopy for pediatric FAI is now established as a safe procedure however there is a paucity of evidence reporting on outcome improvement after arthroscopic treatment of FAI in this population. METHODS: A prospective institutional hip preservation registry was reviewed to identify hip arthroscopies performed for pediatric FAI. Patients with pre-existing hip conditions such as slipped capital femoral epiphysis and Legg-Calve-Perthese were excluded. Included patients were 18 years and younger. The modified Harris Hip Score (mHHS), the Hip Outcome Score (HOS) and the international Hip Outcome Tool (iHOT-33) are routinely collected as part of the registry. Minimal clinically important difference (MCID) was calculated using a distribution based method and substantial clinical benefit (SCB) was calculated using the an anchor question. Receiver operating characteristic (ROC) analysis with area under the curve was used. AUC > 0.7 was considered significantly predictive. RESULTS: Forty-seven children and adolescents were identified. The majority of patients were female (N=32, 68.1%) with a mean age of 16.5 (+ 1.1) years. The MCID (% achieving) for the mHHS, HOS activities of daily living (ADL), HOS Sport and iHOT-33 was 9.5 (85%), 9.8 (79%), 12.1 (85%) and 10.7 (94%) respectively. MCID values on these outcome tools were comparable to adult patients within the registry however for each outcome measure pediatric patients were more likely to achieve MCID. In univariate analysis acetabular version was the only predictive variable for achieving MCID in pediatric FAI (p<0.05). The majority of children (91%) reported improved physical ability based on the anchor question and 53% (compared to 40% in adult registry patients) were classified as achieving SCB. The following one-year raw outcome scores were significantly predictive of SCB on the mHHS, HOS ADL, HOS Sport and mHHS respectively (AUC): 93.5 (0.79), 98.5 (0.84), 96.9 (0.81), 85.9 (0.76). These pediatric SCB values were all higher than SCB values for adult registry patients (82.5, 93.3, 84.4, 63.5 respectively) CONCLUSION: Pediatric patients undergoing arthroscopic FAI treatment can achieve meaningful outcome improvement and compared to adults, a larger proportion of children achieve meaningful outcome improvement. Additionally, while MCID values are comparable in children and adults, children appear to require substantially higher overall post-operative scores to perceive SCB. These findings highlight that commonly administered adult FAI outcome tools may have a relative ceiling effect in capturing outcome after treatment of pediatric FAI.